Psychological Ownership in Online Brand Communities: Scale Development and Validation - Zhang, Rong Mei (Auckland University of Technology, 2020)
“Mine is a small word…. It is deceptive in its power and importance…. It controls our behaviour, but we rarely notice, as we move about our world restricting ourselves to narrow walkways and to those places for which we have keys.” (Rudmin, 1994, p. 55) The quote above mirrors that ownership can influence an individual’s behaviour. Psychological ownership (PO) is a psychological aspect of ownership that reflects a close bond between an individual and their possessions. Organisational scholars contributed to its conceptualisation and scale development and there has been a massive adoption of the concept in marketing research. However, scholars have continued to debate its dimensionality and measurement. Marketing scholars in particular have questioned the use of the concept in an online marketing context, suggesting that there is a need to extend the theory to fully encompass both individual and collective levels of the PO phenomenon in online marketing research. This thesis aims to 1) explore the theoretical notion of PO in online brand communities, 2) establish a PO measurement in the online marketing context, 3) examine the effects of PO in online brand communities. To achieve these objectives, the present study was undertaken in three research phases with a mixed-method design. First, a qualitative study involving online observation, a collage projective technique (i.e., collage), and in-depth interviews was conducted to explore the meaning and dimensions of PO in online communities. The results informed an initial scale development item pool for the second research phase, in which a quantitative study using a survey was conducted to assess the measurement. In the third research phase, the scale was implemented to test the effect of PO on consumers’ online brand community commitment, brand commitment, and brand attachment. Results of the qualitative study that included nine online observations and 10 in-depth interviews suggested a conceptual framework for PO made up of two levels of PO: the individual level of PO (IPO); and collective level of PO (CPO). Eight dimensions were proposed that included five IPO dimensions (sense of gratification, sense of trust, sense of belonging, sense of duty, sense of pride) and three CPO dimensions (sense of affinity, sense of unity, sense of power). The research results from quantitative studies of 421 online brand community members provided support for the dimensions. The findings reported that both levels of PO could positively and directly influence consumers’ online brand community commitment. The consumers who had a strong sense of PO towards the community were more likely to commit to the community. Further, both levels of PO were also found to directly influence consumers’ brand commitment and brand attachment. Consumers who developed a strong feeling of PO towards the online brand community were likely to commit and attach to the focal brand. Also, the consumers with IPO were more likely to commit to the community and the brand, and more likely to attach to the brand than consumers with a sense of CPO to the community. This thesis contributes to the PO literature in the online marketing context. The study developed and empirically validated a conceptual model of PO and a measurement scale in the context of an online community. The thesis also has implications for online brand community management. PO can be seen as a means of retaining online brand community members. Specifically, the marketer can monitor and influence online brand community members’ state of PO by shaping certain underly dimensions. They can also apply the scale to examine their online community members' PO states to predict consumers’ attitudes to the community and the brand.
Keywords: Psychological ownership; Online brand community; Scale development; Online psychological experiences